BAGAIMANAKAH PREFERENSI WISATAWAN DUNIA TERHADAP DESTINASI WISATA DI KAWASAN TIMUR INDONESIA? (STUDI DI HOTEL AMANWANA RESORT PULAU MOYO PULAU MOYO KABUPATEN SUMBAWA) - Subhan Purwadinata; Tuti Handayani; Budiman; Ali Akbar Hidayat (Juremi: Jurnal Riset Ekonomi, 2024)
World tourism destination in Eastern Indonesia (KTI), especially in the region of Pulau Moyo (Moyo Island) Sumbawa regency has been known world, as evidenced by officials and world celebrities come to Sumbawa to relieve fatigue with family. This tourist destination has been able to adapt to all the demands of change by always listening to opinions from various parties, especially tourists who have different preferences in travel. Tourism is closely related to travel, namely the change of temporary residence of a person outside his / her residence. The needs of tourists, people who travel, will affect the development of tourism facilities in certain tourist destinations. Tourism facilities is one important element forming tourism products that play a role to support the ease and convenience of tourists in travel. This study aims to identify the preferences of tourists to tourism facilities of the island of Moyo Sumbawa. The method of analysis in this study is descriptive Quantitative analysis by conducting the data from respondent with the visitors who come travel to the island of Moyo Sumbawa both foreign tourists and domestic tourists. The results of this study indicate that the preferences of tourists in choosing a means of tourism is influenced by tourist destination, price perception of hotel, and facility of hotel influenced the tourists to Moyo Island. Empirical results show that the attraction of tourists to the island of Moyo Sumbawa more due to the privacy of visitors is very awake and a very exotic natural scenery that causes visitors are interested and have implications for the preferences of tourists.